2021
DOI: 10.1182/blood-2021-146832
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Vaccination with BNT162b2, mRNA-1273, and ChADOx1 in Patients with Myeloid and Lymphoid Neoplasms

Abstract: Background: In general, patients with hematological diseases are predisposed to develop infections. Severe COVID-19 infection associated with high mortality is more likely in these patient cohorts compared to the general population. Due to immune defects related to the primary disease and/or to immunosuppressive treatment regimes, vaccination efficacy may be reduced in patients with hematological diseases. So far, data on this area are limited. Aim: To evaluate vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An unconventional technique of delivering vaccines that uses intranasal administration of naked mRNA has been shown to be successful [41]. If mRNA is injected directly into secondary lymphoid tissue, antigen-presenting cells are able to skip the necessity for DC migration and be directed straight to the site of T cell activation [248]. Numerous studies have demonstrated that naked mRNA delivered via intranasal injection is selectively taken up by DCs and has the ability to generate potent antitumor T cell responses, either for therapeutic or preventative purposes [249].…”
Section: Direct Injection Of Mrna Cancer Vaccinesmentioning
confidence: 99%
“…An unconventional technique of delivering vaccines that uses intranasal administration of naked mRNA has been shown to be successful [41]. If mRNA is injected directly into secondary lymphoid tissue, antigen-presenting cells are able to skip the necessity for DC migration and be directed straight to the site of T cell activation [248]. Numerous studies have demonstrated that naked mRNA delivered via intranasal injection is selectively taken up by DCs and has the ability to generate potent antitumor T cell responses, either for therapeutic or preventative purposes [249].…”
Section: Direct Injection Of Mrna Cancer Vaccinesmentioning
confidence: 99%
“…Indeed, the antibody production after vaccination is critically lower in hematologic patients, especially in those with lymphoid neoplasms. In a study shown by Rotterdam et al, 36% of patients tested negative for vaccine‐related antibodies 29 . However, there were specific concerns in patients with mastocytosis regarding severe adverse reactions 30 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study shown by Rotterdam et al, 36% of patients tested negative for vaccine‐related antibodies. 29 However, there were specific concerns in patients with mastocytosis regarding severe adverse reactions. 30 Nevertheless, these have been shown to be rare and broad use of Covid‐19 vaccination in patients with mastocytosis can be recommended, considering known or suspected allergies against components of the vaccine and general and specific safety measures in patients with mastocytosis.…”
Section: Introductionmentioning
confidence: 99%